PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021 - Eni Widiyawati; Maralus Samosir; Malem Ukur Simangunsong (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2022)
This study was conducted to examine the effect of Receivable Turnover and Inventory Turnover variables on Profitability of Food and Beverage companies listed on the Indonesia Stock Exchange in 2018-2021. The data used in this study were obtained from financial reports published by IDX, which were taken from the website www.idx.co.id as well as from the research sample website. The population taken is 33 food and beverage companies listed on the IDX in 2018-2021. The sampling technique used was a purposive sampling technique so that there were 19 research samples. The analytical method used in this research is descriptive statistical analysis, multiple linear regression analysis test and classical assumption test including normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The results of the study show that Accounts Receivable Turnover and Inventory Turnover simultaneously or simultaneously affect the profitability of food and beverage companies listed on the Indonesia Stock Exchange in 2018-2021. Separately, Accounts Receivable Turnover has a positive or significant effect on Profitability while Inventory Turnover has no effect on Profitability in food and beverage companies listed on the IDX in 2018-2021.